Commentary: Reflections on Some Dangers to Childhood Creativity (LEARNing Landscapes, 2012)
In this commentary, renowned author and psychologist Mihaly Csikszentmihalyi reflects on the state of creativity in today’s children. From his many years of studying creativity, Dr. Csikszentmihalyi has observed that the most creative people share a common experience in childhood: that of being left alone, often in a barren environment, and of being bored. Paradoxically, solitude and boredom become the springboard from which a creative passion is born. Finally, the author questions whether the presence of technology in children’s lives today is an opportunity for learning or a source of effortless experiences that are not conducive to nurturing creativity
Keywords: childhood; creativity; bored; solitude; technology; learning